International Encyclopedia of the Social &Amp; Behavioral Sciences 2015
DOI: 10.1016/b978-0-08-097086-8.31109-6
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Immigrants

Abstract: This article reviews the evolution of the concept of assimilation in American social science. It distinguishes assimilation from accommodation as modal adaptation outcomes of different immigrant generations, as well as various aspects that are commonly conflated by the concept (cultural adaptations, economic mobility, social acceptance into a native mainstream); discusses interrelated cultural (subtractive and additive acculturation), structural (primary and secondary integration), and psychological (identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…At the same time, studies on migrant adaptation processes have indicated that differences between migrants and non-migrants diminish over time (Gordon 1964;Rumbaut 2015). Immigrants and their descendants will gradually incorporate the dominant norms of the host country and adapt to its institutional setting.…”
Section: Resourcesmentioning
confidence: 99%
“…At the same time, studies on migrant adaptation processes have indicated that differences between migrants and non-migrants diminish over time (Gordon 1964;Rumbaut 2015). Immigrants and their descendants will gradually incorporate the dominant norms of the host country and adapt to its institutional setting.…”
Section: Resourcesmentioning
confidence: 99%
“…Particularly as far as Vignette B -portraying an elderly mother living in the same country as her children -is concerned, the majority of respondents associated the primary responsibility to be on the daughter. In this sense, the multivariate results indicate that respondents who either were born in Italy or migrated before age 6 are considerably more likely to hold gender-neutral views on the division of informal care work, thus highlighting the relevance of an acculturation pattern on this dimension (see also Maxwell, 2010;Merz et al, 2009;Rumbault, 2015). Next, once more we found evidence of the interplay of gender and religion: being both a woman and religious is associated with a stronger adherence to more traditional non-gender neutral division of care work within the enlarged family.…”
Section: Resultsmentioning
confidence: 90%
“…Participants attempted to acculturate into white-centered spaces to feel included and accepted at predominately white schools and communities. That said, adolescents made conscious efforts to integrate into these spaces through extracurricular activities, clothing styles, and interracial friendships (e.g., Durkee et al, 2019;Rumbaut, 2015). However, only some adolescents were successfully welcomed in whitecentered spaces.…”
Section: Discussionmentioning
confidence: 99%